Sudan Famine Crisis in International Media - Nurhidayah, Elva; Basid, Abdul (Institut Agama Islam Negeri Palopo, 2024)
The Sudan crisis is an important topic that reflects global humanitarian challenges, yet there is a gap in the literature regarding media representations of this issue. This study aims to uncover how two media outlets, royanews.tv and Aljazeera, portray the famine crisis in Sudan, with a focus on the role of the United States and its geopolitical impact. The method used is a qualitative descriptive approach, with data collection techniques through text analysis of two news reports. The main findings show that the media plays a significant role in shaping public perceptions by using attention-grabbing terms such as